2022
DOI: 10.3390/ijms23105508
|View full text |Cite
|
Sign up to set email alerts
|

Tyrosine Kinase Src Is a Regulatory Factor of Bone Homeostasis

Abstract: Osteoclasts, which resorb the bone, and osteoblasts, which form the bone, are the key cells regulating bone homeostasis. Osteoporosis and other metabolic bone diseases occur when osteoclast-mediated bone resorption is increased and bone formation by osteoblasts is decreased. Analyses of tyrosine kinase Src-knockout mice revealed that Src is essential for bone resorption by osteoclasts and suppresses bone formation by osteoblasts. Src-knockout mice exhibit osteopetrosis. Therefore, Src is a potential target for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 93 publications
0
10
0
Order By: Relevance
“…Osteoporosis is a disorder characterized by the deterioration of the bone tissue, and mainly due to the impairment of bone homeostasis, where SRC plays a central role (it promotes bone resorption by osteoclasts and suppresses bone formation by osteoblasts 9 ), as it is also described in the Reactome pathway R-HAS-8940973 (RUNX2 regulates osteoblast differentiation).…”
Section: Resultsmentioning
confidence: 99%
“…Osteoporosis is a disorder characterized by the deterioration of the bone tissue, and mainly due to the impairment of bone homeostasis, where SRC plays a central role (it promotes bone resorption by osteoclasts and suppresses bone formation by osteoblasts 9 ), as it is also described in the Reactome pathway R-HAS-8940973 (RUNX2 regulates osteoblast differentiation).…”
Section: Resultsmentioning
confidence: 99%
“…Among the many signaling pathways involved in cardiac hypertrophy, Src proteins are mainly involved in integrin and G proteincoupled receptor-mediated signaling pathways [11] . A related study shows that knockdown of Src kinase attenuates myocardial brosis and cardiac hypertrophy in vaso-activated mice [12] . This study con rmed the involvement of Src kinase in the hypertrophic process of exercising cardiomyocytes by immunohistochemistry, providing important information for further studies of the exercising heart.…”
Section: Discussionmentioning
confidence: 98%
“…C-Src is a key tyrosine kinase in osteoclasts that regulates ruffling formation, bone cell adhesion, and bone resorption [22]. Park et al found that the link of c-Src to the RANK signaling cascade is essential for osteoclasts to resorb bone [23].…”
Section: Discussionmentioning
confidence: 99%